Parenthesis. - Omiwale, Olaniyi (New England Review (10531297), 2026)
The article centers on a social gathering in Lagos, exploring how the event serves as a microcosm for the city’s complex social dynamics, personal histories, and moral reckonings. Through the interactions of diverse attendees—including a writer launching a book about societal "margins," an artist recently returned from abroad, a lawyer with transnational ties, and a young DJ—the narrative reveals themes of obligation, reputation, memory, and the negotiation of identity within a city marked by both chaos and intimacy. The party functions as a space where private vocabularies and public performances intersect, allowing participants to confront personal debts, social expectations, and the possibility of change. Ultimately, the gathering illustrates how human connection in Lagos is both a fragile and persistent practice of empathy, repair, and ongoing negotiation rather than a source of definitive transformation.